Assessing the Impact of International Cash Accounting Standards on Financial Statements of Enterprises - Eshonqulov, Akmal Qudratovich (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
The adoption of international cash accounting standards by enterprises has become an important topic in the accounting and finance literature. This study assesses the impact of these standards on the financial statements of a sample of enterprises, including their net income, total working capital, and cash flows. The study finds that the adoption of international cash accounting standards leads to improvements in financial reporting quality, including increases in net income, total working capital, and cash flows from operating activities. The study also discusses the advantages and disadvantages of adopting these standards and provides recommendations for improving cash accounting in enterprises based on international standards. Overall, this study contributes to our understanding of the impact of international cash accounting standards on enterprises and provides valuable insights for practitioners, policymakers, and researchers.